2016
DOI: 10.1039/c6ra24026g
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate compounds as green corrosion inhibitors: electrochemical, XPS, DFT and molecular dynamics simulation studies

Abstract: Corrosion inhibition effect of 5,6-bis(2-(1H-benzo[d]imidazol-2-yl)hydrazono)hexane-1,2,3,4-tetraol (BIHT) and 5,6-bis(2-(1-methyl-1H-imidazol-2-yl)hydrazono)hexane-1,2,3,4-tetraol (MIHT) on N80 steel in 15% HCl was measured by electrochemical method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Yadav et al . 17 , prepared two carbohydrate compounds namely BIHT and MIHT as green inhibitors for N80 steel in the aforementioned HCl concentration. It was revealed that the chemisorbed inhibitor (BIHT) had the highest IE % of 94.8% at 30 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Yadav et al . 17 , prepared two carbohydrate compounds namely BIHT and MIHT as green inhibitors for N80 steel in the aforementioned HCl concentration. It was revealed that the chemisorbed inhibitor (BIHT) had the highest IE % of 94.8% at 30 °C.…”
Section: Introductionmentioning
confidence: 99%
“…With the enhancement of environmental consciousness, designing eco-friendly corrosion inhibitors has gained tremendous momentum. [18][19][20][21][22] Due to the features of non-toxicity and high safety, green polymer inhibitors have attracted much attention. An overview on the use of carbohydrate polymers as corrosion inhibitors for metal materials in different media has been summarized by Umoren and Eduok.…”
Section: Introductionmentioning
confidence: 99%
“…To study the chemical reactivity of inhibitor molecules, the analysis of the energy of the highest occupied molecular orbital ( E HOMO ) and the energy of the lowest unoccupied molecular orbital ( E LUMO ) has been studied. According to FMO theory, E HOMO is related to the capacity of a molecule to donate electrons, and the higher the value of E HOMO, higher would be the electron-donating tendency of the molecule [ 71 73 ]. Higher E LUMO represents the ability of the molecule to accept electrons, whereas lower values of E LUMO indicates more probably the ability of the molecule to accept electrons [ 74 ].…”
Section: Resultsmentioning
confidence: 99%